The Use of Sentences in Scientific Research Articles - Sultan, Sultan (Indonesian Journal of Educational Studies, 2013)
This study aimed to describe the level of readability, construction, and the effectiveness of sentences in research articles. The research data come from six research articles Makassar State University in 2011. Data collected through technical documentation with read-quoted. The results showed that: 1) the level of readability sentence in a scientific article written lecturers lower category, 2) construction of the phrase commonly used active form; 3) the ineffectiveness of the sentence, include: incoherence, confusion, incomplete elements, error passive, disunity ideas, and ketidakparalelan.